2018
DOI: 10.1016/j.ntt.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal phthalate exposure and language development in toddlers from the Odense Child Cohort

Abstract: Our findings are notable, as adverse associations were suggested even in this low-level exposed population, with only one spot urine sample for exposure assessment and control for confounders. Lower scores in early language development are of relevance to health as this test predicts later educational success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 55 publications
0
31
0
2
Order By: Relevance
“…Finally, we measured mono-benzyl phthalate (MBzP) and monoethyl phthalate (MEP). Moderate to high correlation between all summed metabolites has been shown elsewhere [23]. Preparation and storage of standard solutions and samples, instrumental LC-MS/MS analysis and general method validation has previously been described [22].…”
Section: Phthalate Metabolite Measurementsmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, we measured mono-benzyl phthalate (MBzP) and monoethyl phthalate (MEP). Moderate to high correlation between all summed metabolites has been shown elsewhere [23]. Preparation and storage of standard solutions and samples, instrumental LC-MS/MS analysis and general method validation has previously been described [22].…”
Section: Phthalate Metabolite Measurementsmentioning
confidence: 92%
“…Likewise, the 4 measured DiNP metabolites; mono-iso-nonyl phthalate (MiNP), monohydroxy-iso-nonyl phthalate (MHiNP), mono-oxo-iso-nonyl phthalate (MOiNP) and mono-carboxy-iso-octyl phthalate (MCiOP) were measured and summed as ΣDiNP m . We measured mono-iso-butyl phthalate (MiBP) and mono-nbutyl phthalate (MnBP) and combined them as MBP i + n , since the two metabolites have been shown to be highly correlated in the urine of the women of Odense Child Cohort [22,23]. Finally, we measured mono-benzyl phthalate (MBzP) and monoethyl phthalate (MEP).…”
Section: Phthalate Metabolite Measurementsmentioning
confidence: 99%
“…Importantly, the relationship between BPA exposure and language development as an independent outcome and not a part of IQ has not been previously assessed. In a previous study among 518 mother-child pairs from the Odense Child Cohort, we found associations between higher maternal phthalate exposure and poorer language development in 20-36 months old boys, whereas no association was found in girls (Olesen et al 2018). We therefore wanted to explore if this association was also found for prenatal BPA exposure.…”
Section: Introductionmentioning
confidence: 91%
“…Both animal studies and epidemiology have linked phthalates to the developmental neurotoxicity of DEHP (see for instance [133,134]). Regarding DBP, in adults, a recent experiment reported a possible disruption of the thyroid axis in men following DBP exposure [103].…”
Section: Phthalatesmentioning
confidence: 99%